Tailoring the Properties of UiO-66 through Defect Engineering: A Review - Feng, Yi; Chen, Qian; Jiang, Minqi; Yao, Jianfeng (Industrial & engineering chemistry research, 2019)
Defects, which are commonly in metal organic frameworks (MOFs), are closely related to the performance of materials in various applications. Unlike other MOFs where metal ion clusters are usually 4-, 5-, or 6-connected to the organic linkers, one secondary building unit (SBU) of UiO-66 is coordinated by 12 Zr6 clusters via 12 benzen-1,4-dicarboxlate (BDC) linkers. Therefore, the integrity of the structure can be well maintained after linker or even cluster missing. So far, many methods have been reported on the defect engineering of UiO-66 including adjusting the synthesis conditions (temperature, Zr/linker ratio and choice of Zr precursor), addition of modulators, thermal activation/dehydration, linker modification and metal cation substitution. Various techniques have been used and developed to characterize the existence and concentration of defects, though each technique has its limitations. The formation of defects not only changes the pore structure, but also brings beneficial changes in thermal, electronic, catalytic and adsorbing abilities; thus improved performance can be achieved when defective UiO-66 is used as Lewis and/or Brönsted acids, photocatalysts, adsorbents, electrodes or porous support. In this review, a comprehensive review of defect engineering for UiO-66 including their preparations, characterizations, applications, and then the challenges and outlook are discussed, aiming to provide some designing knowledge for the synthesis of defective UiO-66 with high-performance and promote the wide application of UiO-66 in various fields.